Global named patient use program of afatinib in advanced non-small-cell lung carcinoma patients who progressed following prior therapies. (June 2018) - Cappuzzo, Federico; Soo, Ross; Hochmair, Maximilian; Schuler, Martin; Lam, Kwok Chi; Stehle, Gerd; Cseh, Agnieszka; Lorence, Robert M; Linden, Stephan; Forman, Nicole D; Hilbe, Wolfgang; Jazieh, Abdul Rahman; et al.
Aim: A global afatinib named patient use program in non-small-cell lung carcinoma (NSCLC) commenced in 2010.Materials & methods: Eligible NSCLC patients had progressed after clinical benefit on prior erlotinib/gefitinib and/or had activating EGFR / HER2 mutations, exhausted all other treatments, and were ineligible for afatinib trials.Results: Data, as of January 2016, were reported on 3966 heavily pretreated NSCLC patients (41 countries; six continents). Among 2595/3966 (65.4%) patients with tumor EGFR status, 2407 (92.8%) were EGFR mutation positive. Median time to treatment failure (2862/3966 [72.2%] patients with available data) was 4.4 months. Among 1141/2862 (39.9%) patients with response reported, objective response rate was 23.4% (267/1141). Safety findings were as expected.Conclusion: Time to treatment failure durations and objective response rates were encouraging.